The Development of a One-Step PCR Assay for Rapid Detection of an Attenuated Vaccine Strain of Duck Hepatitis Virus Type 3 in Korea - Cheng-Dong Yu; Jong-Yeol Park; Sang-Won Kim; Yu-Ri Choi; Se-Yeoun Cha; Hyung-Kwan Jang; Min Kang; Bai Wei (Veterinary Sciences)
Duck hepatitis A virus type 3 (DHAV-3) is a viral pathogen that causes acute, high-mortality hepatitis in ducklings, and vaccination with attenuated live vaccines is currently the main preventive measure against it. However, differentiating infected from vaccinated animals (DIVA) is crucial for clinical diagnosis and effective disease control. This study aimed to develop a rapid mismatch amplification mutation assay PCR (MAMA-PCR) diagnostic method to simultaneously detect and differentiate between wild-type and vaccine strains. The method was specifically designed to target the critical single-nucleotide polymorphism (SNP) site (T→C at position 1143 in the VP0 gene) unique to the Korean vaccine strain AP04203-P100. MAMA-PCR demonstrated high sensitivity and specificity, with detection limits as low as 102.4 ELD50/mL for wild strains and 100.5 ELD50/mL for vaccine strains, and showed no cross-reactivity with 11 other common duck pathogens. The clinical sample results were completely consistent with those obtained using nested PCR detection and gold-standard sequencing. In summary, we successfully developed a rapid, one-step MAMA-PCR method that is more suitable for clinical diagnosis than traditional sequencing methods.